Is Affective Intentionality Necessarily Irrelevant in Social Cognition? - Sarah Songhorian (Rosenberg & Sellier, 2016)
The aim of this work is to understand the meaning and the extent of “affective intentionality”, to discover whether or not it is analogous to other concepts of intentionality and if it can play a role in social cognition. I will compare Searle’s conception of intentionality, in particular affective intentionality, with Scheler’s concept of sympathy. The reason for this is that I believe the comparison shows that it is not always necessary to presuppose something to have affective intentionality.